The Role of Anticipatory Socialization as A Mediating Variable between The Big Five Personality Traits and Professional Skepticism - Tresna Adinda Regbiyantari; Niluh Putu Dian Rosalina Handayani Narsa (Universitas Airlangga, 2021)
This study analyzes the relationship between the Big Five personality traits and professional skepticism, between professional skepticism and anticipatory socialization, and the relationship between the Big Five personality traits and anticipatory socialization using professional skepticism as the mediating variable. The research data were obtained from 187 questionnaires distributed to accounting students. The results in this study prove that there is a positive relationship between the characteristics of extraversion, agreeableness, conscientiousness, and openness, on anticipatory socialization. Meanwhile, the character of neuroticism has no relationship with anticipatory socialization. In addition, it was also found that there was an indirect, positive relationship between neuroticism, extraversion and conscientiousness, and anticipatory socialization through professional skepticism. This research is expected to provide insights for accounting students as they start preparing to become good auditors while in college.